Chlorophyll’s dependency towards electrical characteristics of ananas comosus waste-based dye-sensitized solar cell - Alyaa Afiqah, Fauzi; Norazwina, Zainol; Faiz, Arith; Khumaeni, Ali; Ahmad Syahiman, Mohd Shah (Semarak Ilmu Publishing, 2026)
The presence of chlorophyll in the Ananas Comosus waste is useful in the fabrication of Dye Sensitized Solar Cell (DSSC) which is an alternative technology of solar cell. The purpose of the research is to fabricate DSSC from the waste. Mechanical extraction is applied here to extract the chlorophyll from the waste by using a saccharum machine. Ultraviolet-Visible Spectrophotometer (UV-VIS) is used to measure the content of chlorophyll a and chlorophyll b. The expected result of this experiment is to achieve higher chlorophyll content which is able to absorb more light energy from the sunlight. The extraction time to collect the juice sample is 3 times. The content of chlorophyll will eventually decrease if it is stored unused for a long period. DSSC will be fabricated with doped Titanium Dioxide, TiO2 which are based on natural dyes from Malaysia tropical fruits, wherein contain chlorophyll which enhances the photosensitization effect due to the high interaction on the surface of the film. Such a natural dye extracted from Ananas Comosus can be subjected to molecular tailoring to give a superior dye preparation, offering a wide range of spectral absorption, covering the entire visible region (400 – 700 nm). Furthermore, the additive (4-tert-butylpyridine) in potassium iodide, KI electrolyte, affects the rate of electron injection into the oxidized dye sensitizer. Fluorine-doped tin oxide (FTO) conductive glass will be used to fabricate the solar cells. After the fabrication process is done, the solar cell was measured by multimeter to obtain the value of output voltage.